Differentiation of Progressive Supranuclear Palsy: clinical, imaging and laboratory tools. (13th February 2013) - Liscic, R. M.; Srulijes, K.; Gröger, A.; Maetzler, W.; Berg, D.
<x xml:space="preserve">Abstract</x> Progressive supranuclear palsy (PSP) is the most common atypical parkinsonian syndrome comprising two main clinical subtypes: Richardson's syndrome (RS), characterized by prominent postural instability, supranuclear vertical gaze palsy and frontal dysfunction; and PSP‐parkinsonism (PSP‐P) which is characterized by an asymmetric onset, tremor and moderate initial therapeutic response to levodopa. The early clinical features of PSP‐P are often difficult to discern from idiopathic Parkinson's disease (PD), and other atypical parkinsonian disorders, including multiple system atrophy (MSA) and corticobasal syndrome (CBS). In addition, rare PSP subtypes may be overlooked or misdiagnosed if there are atypical features present. The differentiation between atypical parkinsonian disorders and PD is important because the prognoses are different, and there are different responses to therapy. Structural and functional imaging, although currently of limited diagnostic value for individual use in early disease, may contribute valuable information in the differential diagnosis of PSP. A growing body of evidence shows the importance of CSF biomarkers in distinguishing between atypical parkinsonian disorders particularly early in their course when disease‐modifying therapies are becoming available. However, specific diagnostic CSF biomarkers have yet to be identified. In the absence of reliable disease‐specific markers, we provide an update of the recent literature on the assessment of clinical symptoms, pathology, neuroimaging and biofluid markers that might help to distinguish between these overlapping conditions early in the course of the disease.